2015
DOI: 10.1515/amm-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Piv Method and Numerical Computation for Prediction of Liquid Steel Flow Structure in Tundish

Abstract: This paper presents the results of computer simulations and laboratory experiments carried out to describe the motion of steel flow in the tundish. The facility under investigation is a single-nozzle tundish designed for casting concast slabs. For the validation of the numerical model and verification of the hydrodynamic conditions occurring in the examined tundish furniture variants, obtained from the computer simulations, a physical model of the tundish was employed. State-of-the-art vector flow field analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…The previously presented results on the flow hydrodynamics for the analysed tundish showed that in the current configuration of the tundish equipment, there are two areas of vertical recirculation distributed more or less symmetrically with respect to the longitudinal axis. In addition, in earlier works, it was observed that in the central part of the tundish, the hydrodynamic field is subject to periodic fluctuation [35,47]. Therefore, in the current work, the flow fields at the interaction site of water with the tracer were recorded and the fluctuation level was recorded.…”
Section: Experiments Results and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The previously presented results on the flow hydrodynamics for the analysed tundish showed that in the current configuration of the tundish equipment, there are two areas of vertical recirculation distributed more or less symmetrically with respect to the longitudinal axis. In addition, in earlier works, it was observed that in the central part of the tundish, the hydrodynamic field is subject to periodic fluctuation [35,47]. Therefore, in the current work, the flow fields at the interaction site of water with the tracer were recorded and the fluctuation level was recorded.…”
Section: Experiments Results and Discussionmentioning
confidence: 85%
“…The physical glass model of tundish was made on a scale of 2:5 (Figure 1(b)). The linear scale of the model ensures geometric similarity to the real facility, whereas the dynamic similarity was ensured by Froude criterion generally applied to traditional investigations for the development of continuous casting technology [34][35][36][37][38][39][40][41]. Within the project being implemented, the test stand has been retrofitted with the planar laser-induced fluorescence system (PLIF), sCMOS camera and third harmonic optics supplied by Dantec Dynamics.…”
Section: Methodology and Experiments Conditionsmentioning
confidence: 99%
“…Digital image measurement technology can not only achieve the overall structure and transient image field, but also obtain the velocity data of the whole flow field quantitatively. Some researchers [7][8][9] have measured the flow field in the tundish by the particle image velocimetry (PIV), thus that the overall structure and transient image of a planar flow field was obtained quantitatively.…”
Section: Of 10mentioning
confidence: 99%
“…Therefore, tin, like major industrial metals with abundance in the earth’s crust below 0.0002%, required additional insight into fundamental knowledge on tin metallurgy [ 22 , 23 ]. This research work presents results related to hydrodynamic structures developing in batch reactors, different in shape, recorded by means of the particle image velocimetry (PIV) method [ 24 , 25 , 26 , 27 ]. Particle image velocimetry is the non-invasive method for predicting hydrodynamics wherever the testing objects and fluids are transparent.…”
Section: Introductionmentioning
confidence: 99%